1989
DOI: 10.1200/jco.1989.7.3.387
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of optimal duration of chemotherapy in favorable-prognosis disseminated germ cell tumors: a Southeastern Cancer Study Group protocol.

Abstract: Four courses of PVP16B (cisplatin plus etoposide [VP-16] plus bleomycin) has been standard chemotherapy for disseminated germ cell tumors at Indiana University and the Southeastern Cancer Study Group (SECSG) since 1984. We began a random prospective phase III study in patients with favorable-prognosis (minimal and moderate extent) disseminated germ cell tumors comparing four courses of PVP16B over 12 weeks to the identical dose PVP16B administered in three courses over 9 weeks. The categories of minimal and mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
112
0
6

Year Published

1995
1995
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 357 publications
(119 citation statements)
references
References 7 publications
1
112
0
6
Order By: Relevance
“…The EORTC/ MRC trial with 812 patients comparing 3 to 4 cycles of BEP chemotherapy found equivalent efficacy and toxicity between the two arms (de Wit et al, 2001). An earlier US trial compared 3 and 4 cycles of BEP in 184 patients and found similar survival but less toxicity with the shorter treatment arm (Einhorn et al, 1989).…”
Section: Discussionmentioning
confidence: 96%
“…The EORTC/ MRC trial with 812 patients comparing 3 to 4 cycles of BEP chemotherapy found equivalent efficacy and toxicity between the two arms (de Wit et al, 2001). An earlier US trial compared 3 and 4 cycles of BEP in 184 patients and found similar survival but less toxicity with the shorter treatment arm (Einhorn et al, 1989).…”
Section: Discussionmentioning
confidence: 96%
“…Only a minority of the patients (13.5%) relapsed. Previous studies reported a relapse rate ranging between 6% and 14% (Einhorn et al, 1989 et al. 1998;de Wit et al, 2001;Bokemeyer et al, 2004;Kondagunta et al, 2005;Culine et al, 2007;Grimison et al, 2010).…”
Section: Discussionmentioning
confidence: 97%
“…In the previously-m entioned study of 184 patients w ho received either three or four BEP cycles, one patient died from chem o th erap y -related sep sis. 19 As it apco n sid ered the gold stan d ard c h e m o th e ra p y in pears from this latter study that the efficacy of three…”
Section: Cisplatin Vs Carboplatinmentioning
confidence: 93%